Soziale Selbstkonzepte von Kindern im Grundschulalter und ihre Einstellungen gegenüber Peers mit Förderbedarf in der sozial-emotionalen Entwicklung - Löper, Marwin Felix; Hellmich, Frank (Sonderpädagogik zwischen Wirksamkeitsforschung und Gesellschaftskritik)

Inklusiver Unterricht in der Grundschule

Aktuelle Fragestellungen zu Produktion, Logistik und Controlling

Bitte stimmen Sie jetzt ab! - Ein Erfahrungsbericht über das Audience Response System PINGO - Kundisch, Dennis; Neumann, Jürgen; Schlangenotto, Darius (Proceedings der 15. e-Learning Fachtagung Informatik (DELFI 2017))

Study? Now! - Evaluation einer gamifizierten App zur Überwindung von akademischer Prokrastination - Klingsieck, K.; Bomm, A.; Djawadi, Behnud; Fahr, Rene; Feldotto, M.; John, Thomas; Kundisch, Dennis; Skopalik, A. (Tagung der Fachgruppen Entwicklungspsychologie und Pädagogische Psychologie (PAEPSY))

Decision Taking, Confidence and Risk Management in Banks from Early Modernity to the 20th Century

Mahlzeitenmuster von Eltern in Paarbeziehungen - Klünder, Nina (Care und die Wissenschaft vom Haushalt)

Differenzierte Ermittlung des Gender Care Gap auf Basis der repräsentativen Zeitverwendungsdaten 2012/13 - Klünder, Nina

Essalltag und Arbeitsteilung von Eltern in Paarbeziehungen – Eine quantitative Analyse auf Basis der repräsentativen Zeitverwendungsdaten 2012/13 und 2001/02 - Klünder, Nina; Meier-Gräwe, Uta (Journal of Family Research)
The article examines the division of labor for everyday food routines of two-parent households depending on their labor force participation. Using data from the representative German Time Use Survey 2001/02 and 2012/13, three different pairs were formed: dual-earner couples, couples with additional female income and male-breadwinner couples Findings show that mother’s employment influences the time used for everyday food routines: It was found that the higher the employment rate of mothers, the less time was spent on food routine activities. Furthermore, the daily time used for everyday food routines was reduced from 2001/02 to 2012/13. The largest reductions were seen in the group of mothers working fulltime. Besides that, fathers were more engaged in meal preparation on the weekends, although the responsibility was the mother’s. In addition, the age and number of children in a household influenced the time used for everyday food routines. However, none of the examined pair constellations can help determine an egalitarian division of everyday food routines. There is still a labor division by gender.
Zusammenfassung
Der Beitrag untersucht die zeitliche Gestaltung sowie die innerfamiliale Arbeitsteilung des Essalltags von Müttern und Vätern in Paarbeziehungen differenziert nach deren Erwerbsumfang. Die Sekundäranalyse erfolgt auf Basis der repräsentativen Zeitverwendungsdaten 2012/13 und 2001/02, wobei drei Paarkonstellationen untersucht werden: Doppelverdiener-Paare, weibliche Zuverdiener- Paare sowie Paare mit männlichem Familienernährer. Die Analyse des Essalltags zeigt, dass der Erwerbsstatus der Mutter die zeitliche Gestaltung des Essalltags beeinflusst. Je höher dieser ist, desto weniger Zeit wird für die Ernährungsversorgung aufgewendet. Darüber hinaus hat sich die tägliche Zeitverwendung für die Ernährungsversorgung von 2001/02 bis 2012/13 reduziert, wobei die stärksten Einsparungen bei vollzeiterwerbstätigen Müttern zu konstatieren sind. Väter engagieren sich verstärkt am Wochenende bei der Mahlzeitenzubereitung, gleichwohl liegt die Verantwortung insgesamt bei den Müttern. Ebenso beeinflussen Alter und Anzahl der Kinder die Zeitverwendung für die Ernährungsversorgung. Letztlich kann in keiner untersuchten Paarkonstellation eine egalitäre Arbeitsteilung zur Gestaltung des Essalltags festgestellt werden. Vielmehr dominieren relativ ausgeprägte geschlechtsspezifische Arrangements.

Ausgewählte Ergebnisse der Zeitbudgeterhebungen 1991/92, 2001/02 und 2012/13 - Meier-Gräwe, Uta; Klünder, Nina (Familien stärken, Vielfalt ermöglichen. Bericht der familienpolitischen Kommission der Heinrich-Böll-Stiftung)

Generation Y. Wohin mit der Zeit? Ein empirischer Vergleich zur Zeitverwendung verschiedener Generationen - Zimmermann, Josepha; Klünder, Nina (Hauswirtschaft und Wissenschaft)

Towards a Lean Approach to Gamifying Education - John, Thomas; Feldotto, M.; Hemsen, P.; Klingsieck, K.; Langendorf, Mike (Proceedings of the 24th European Conference on Information Systems (ECIS))

Carbohydrates from Sources with a Higher Glycemic Index during Adolescence: Is Evening Rather than Morning Intake Relevant for Risk Markers of Type 2 Diabetes in Young Adulthood? - Diederichs, Tanja; Herder, C; Roßbach, S; Roden, M; Wudy, SA; Nöthlings, U; Alexy, U; Buyken, Anette (Nutrients)

Achieving More by Paying Less? How Retailers can Benefit by Bidding Less Aggressively in Paid Search Auctions - Schlangenotto, Darius; Kundisch, Dennis (Proceedings of the 24th European Conference on Information Systems (ECIS))

Making Gamification Easy for the Professor: Decoupling Game and Content with the StudyNow Mobile App - Feldotto, M.; John, Thomas; Kundisch, Dennis; Hemsen, P.; Klingsieck, K.; Skopalik, A. (Proceedings of the 12th International Conference on Design Science Research in Information Systems and Technology (DESRIST))

Decomposing the Variance of Online Consumer Ratings and the Impact on Price and Demand - Zimmermann, Steffen; Herrmann, Philipp; Kundisch, Dennis; Nault, Barrie (Workshop Theory in Economics of Information Systems (TEIS))

Using Information Cues to Identify High Quality Ideas in Crowd Evaluation - Görzen, Thomas; Kundisch, Dennis (2nd Workshop on IS Design and Economic Behavior (ISDEB))

Recommendation and Configuration of Value-Added Services for Repurposing Electric Vehicle Batteries: A Vertical Software Prototype - Klör, Benjamin; Monhof, Markus; Bräuer, Sebastian; Beverungen, Daniel (Proceedings of the 19th IEEE Conference on Business Informatics (CBI 2017))

Microservice-based Execution Environment for Service Compositions - Schürmann, Andreas
The microservice architecture uses independently running microservices as build- ing blocks for applications. These microservices are clearly bounded for each other and expose their functionality through, for instance, RESTful application inter- faces. Particularly the clear boundaries between microservices enable the reuse of microservice throughout different projects. Because of the increasing use of microservices, the composition of multiple microservices in service composition becomes a more important task. A challenging area in developing service compo- sitions is that it involves two distinct layers with few junctions. On the one hand, describes a service composition a business process, which involves multiple com- ponents. On the other hand, involves the implementation of a service composition topics like service discovery and message exchange protocols since the microser- vices involved in a service composition are located within a network environment. In this Bachelor’s Thesis, I describe a descriptions language to abstractly describe the business logic of a service composition. Furthermore, I describe a genera- tion process, which compiles this abstract description to a working microservice realizing the specified service composition. In addition to that, I provide an im- plementation of the generation process, as a proof of concept, and test it within a Kubernetes-based cluster environment.

The impact of customer reviews and advertisement efforts on the performance of experience goods in electronic markets - Frick, Bernd; Kaimann, Daniel (Applied Economics Letters)